Efektivitas Penggunaan Metode An-Nahdliyah Dalam Pembelajaran Al-Quran - Tri Marfiyanto; Moh Ismail (EDUCATIO : Journal of Education, 2017)
This research is backed by a phenomenon seeing the tendency of parents put their children to a formal education institution, so that nowadays many Muslim children can not read the Qur'an. The purpose of this research is to explore the use of An-Nahdliyah method in improving the learning ability to read AL-Qur'an. The type of research used is qualitative research. In this research the data collection techniques used are observations, in-depth interviews, documentation, while in analyzing data using reduction, data presentation, and verification. The results showed about the use of An-Nahdliyah method in learning to read the Qur'an in students can improve properly. It is hoped that all parties provide coaching and learning processes. So the quality will increase better